2010
DOI: 10.1002/pssa.200824421
|View full text |Cite
|
Sign up to set email alerts
|

Ternary magnetic nanocomposites based on core–shell Fe3O4/polyaniline nanoparticles distributed in PVDF matrix

Abstract: Magnetic, electric, and radioprotector properties of hybrid nanocomposites of Fe3O4 nanoparticles with and without a shell of polyaniline (PANI), which is doped with dodecylbenzenesulfonic acid (DBSA), dispersed in polyvinylidene fluoride (PVDF) matrix have been studied. It has been found that the presence of PANI–DBSA as a separate filler in the ternary nanocomposite film, which also contains as another filler the core–shell Fe3O4/PANI–DBSA nanoparticles, facilitates dispersion of the magnetic filler due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…For the past 10 years, many studies have shown that the dispersion of ferromagnetic fillers in a diamagnetic matrix gave significant ferromagnetic properties . Especially magnetic nano fillers present exceptional properties such as strong magnetization and high coercive field ( H c ).…”
Section: Introductionmentioning
confidence: 99%
“…For the past 10 years, many studies have shown that the dispersion of ferromagnetic fillers in a diamagnetic matrix gave significant ferromagnetic properties . Especially magnetic nano fillers present exceptional properties such as strong magnetization and high coercive field ( H c ).…”
Section: Introductionmentioning
confidence: 99%
“…Structure differences between the conducting polymer in pure and composite states were confirmed for different (nano)composites [16,17,19,23,25,26,29,[30][31][32][33]. For example, from the XRD-spectra of doped polyaniline and its nanostructured composite with polycarbonate (PC), we found that its degree of crystallinity in the pure state was about 3 times lower, and 6.…”
Section: Structure-property Relationship Of the Nanocompositesmentioning
confidence: 82%
“…[56] Reduction in Q could be due to different reasons such as interparticle interaction, distribution of particle sizes, the presence of various defects, and so on. Petrychuk et al [57] investigated samples containing interacting magnetic nanoparticles forming clusters of different sizes. For small-sized magnetic clusters, the magnetic energy may be small enough to enable thermal energy the enhancement of the superparamagnetic contribution into magnetization.…”
Section: O 4 Nanocomposites In Comparison With Go-fe 3 Omentioning
confidence: 99%